Who First Excavated Stratigraphically? - Jr, William H. Stiebing (The Biblical archaeology review, 1981)
North American Indians left few monuments of their civilization. Early European explorers and settlers in North America found no stone cities or defense walls or water systems or monumental structures built by the native Americans. The only exceptions were large earthen mounds obviously built by humans rather than formed by natural forces. Some of […]